2009
DOI: 10.2174/092986609789839269
|View full text |Cite
|
Sign up to set email alerts
|

The Production and Role of Gastrin-17 and Gastrin-17-Gly in Gastrointestinal Cancers

Abstract: The gastrointestinal peptide hormone gastrin is responsible for initiating the release of gastric acid in the stomach in response to the presence of food and/or humoral factors such as gastrin releasing peptide. However, it has a role in the growth and maintenance of the gastric epithelium, and has been implicated in the formation and growth of gastric cancers. Hypergastrinemia resulting from atrophic gastritis and pernicious anemia leads to hyperplasia and carcinoid formation in rats, and contributes to tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 281 publications
(268 reference statements)
0
22
0
Order By: Relevance
“…progastrin (precursor of gastrin) and glycine-extended gastrin [20], do not stimulate the acid secretion. These peptides can be found in all cells that express the gastrin gene, including colonic, lung, pancreatic, esophageal and gastric cancer cells [22,49,50]. Elevated blood levels of gastrin were shown to correlate positively with pancreatic cancer risk [51].…”
Section: Figure 2 the Correlation Between Epigastric Bloating And Ghmentioning
confidence: 99%
See 2 more Smart Citations
“…progastrin (precursor of gastrin) and glycine-extended gastrin [20], do not stimulate the acid secretion. These peptides can be found in all cells that express the gastrin gene, including colonic, lung, pancreatic, esophageal and gastric cancer cells [22,49,50]. Elevated blood levels of gastrin were shown to correlate positively with pancreatic cancer risk [51].…”
Section: Figure 2 the Correlation Between Epigastric Bloating And Ghmentioning
confidence: 99%
“…Autoimmune reactions, Helicobacter pylori infection and acid suppressing drugs may induce chronic atrophic gastritis and resultant hypochlorhydria, which eventually results in enhanced synthesis of gastrin. Presence of gastrin-secreting tumors, gastrinomas, predisposes to hypergastrinemia [23,36,50]. Elevated level of gastrin is currently recognized as a factor involved in pathogenesis of various gastric malignancies, among them gastric cancer [23,29,35].…”
Section: Figure 2 the Correlation Between Epigastric Bloating And Ghmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasrollahzadeh et al (2011) reported an AUC of 0.77 for G17 to discriminate GA. Kikushi et al (2011) also suggested G17 as good biomarker for diagnosis GA. Regarding the role of G17 pathogenesis of GC (Copps et al, 2009), further studies are warranted to assess the validity of G17 to differentiate GA/GC.…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for initiating gastric acid release in the stomach in response to stimulus. During gastric cancer development, atrophic gastritis and hypergastrinemia have been proposed to be critical factors for both diffuse type and intestinal types of GC (reviewed in Waldum et al, 2017), by stimulating cell proliferation and other mechanisms not completely elucidated (Copps et al, 2009;Smith et al, 2017;Waldum et al, 2017). In children, serum gastrin and gastrin 17 have been reported to be overexpressed in H. pylori infected children in five studies included in this review (Kato et al, 2004;Maciorkowska et al, 2006;Plonka et al, 2006;Czaja et al, 2008;Guariso et al, 2009).…”
Section: Extracellular Secreted Proteinsmentioning
confidence: 98%